2009
DOI: 10.1577/m08-249.1
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Choice by Atlantic Salmon Parr in Relation to Turbulence at a Reach Scale

Abstract: Abstract.-The variables commonly used to describe the physical habitat of Atlantic salmon Salmo salar parr are average velocity, water depth, and substrate. A variety of micro-and mesohabitat models have been developed using these variables to assess habitat quality. However, Atlantic salmon parr live in highly turbulent streams and rivers in which intense fluctuations of water velocity occur. Laboratory experiments have shown that turbulence affects the behavior and energetics of fish. Nevertheless, habitat u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…The morphological and hydrodynamic complexity of natural rivers provides challenges and opportunities for fish, including the avoidance and utilisation of turbulence associated with vortical flows. Swimming mechanics and fish physiology have mainly been observed for laboratory flume studies in which vortices are experimentally generated, for example, around a cylinder (for a review, see Liao, ), but field studies quantifying behavioural responses to turbulence are quickly emerging (Enders et al , ; Cotel et al , ; Enders et al , ).…”
Section: Prospectus and Conclusionmentioning
confidence: 99%
“…The morphological and hydrodynamic complexity of natural rivers provides challenges and opportunities for fish, including the avoidance and utilisation of turbulence associated with vortical flows. Swimming mechanics and fish physiology have mainly been observed for laboratory flume studies in which vortices are experimentally generated, for example, around a cylinder (for a review, see Liao, ), but field studies quantifying behavioural responses to turbulence are quickly emerging (Enders et al , ; Cotel et al , ; Enders et al , ).…”
Section: Prospectus and Conclusionmentioning
confidence: 99%
“…Second, attempts to quantify habitat use by fish in the field typically produce mixed results (e.g. Heggenes et al, 1991;Facey and Grossman, 1992;Jowett and Richardson, 1995;Mäki-Petäys et al, 1997;Cotel et al, 2006;Enders et al, 2009). This is not surprising because space use is influenced by multiple confounding variables impossible to control in situ (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The study shows that only the reach downstream of the Gezhouba Dam meets the spawning requirements for this species of fish. Kozarek et al (2007), Moir and Pasternack (2008) and Enders et al (2009) reported that many efforts have been made to protect and restore river habitats for brown trout (Salmo trutta), Chinook salmon (Salvelinus fontinalis), Atlantic salmon (Salmo salar) and other aquatic animals around the world. Conventional large-scale surveys and historical data on aquatic habitats often are used in these restoration and protection efforts.…”
Section: Discussionmentioning
confidence: 99%